COMPARATIVE ANALYSIS OF TWO DIFFRACTION SCHEMES FOR WIDELY DIVERGENT BEAM OF X-RAY RADIATION - Avetyan, K.T.; Levonyan, L.V.; Semerjyan, H.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
Comparative analysis of two diffraction schemes d-c (diaphragm-crystal) and c-d (crystal-diaphragm) for widely divergent beam of X-ray radiation is conducted. It is justified that in c-d scheme the diffraction image is a topographic map of the studied area of the crystal.